DAMPAK PENERAPAN BEA MASUK ANTI-DUMPING ATAS IMPOR PRODUK TINPLATE - Nurcahyo, Marsanto Adi; Purwana, Aditya Subur (Politeknik Keuangan Negara STAN, 2020)
ABSTRACT:Anti-dumping on tinplate products aim to protect domestic industries. Still, some industries want tinplate products not to be subject to anti-dumping because domestic production is not sufficient. This research examines the application of anti-dumping import duties on tinplate products from China, Taiwan, and Korea from 2014 to 2018, to know whether there are differences in the value of imports before and during the anti-dumping import duty. Use secondary data sourced from UN-Comtrade. Samples are selected by countries that have continuously sent tinplate products to Indonesia from 2010 to 2018, namely China, Taiwan, Korea, Japan, Germany, India, and Malaysia. Using the Mean Equality Test, it is known that there are differences in the import value before and during the anti-dumping import duty, with a p-value of 0.0114 less than Î± (0.05), so it is concluded that there is a difference in the import value of the tinplate product before and during anti-dumping duty. Descriptive analysis results illustrate imports from China and Taiwan tend to decrease. In contrast, imports from Korea tend to increase despite being subjected to anti-dumping duties because they can compete by using preferential tariffs based on free trade schemes.Keywords: Antidumping, Import duty, TinplateABSTRAK:Anti-dumping terhadap produk tinplate bertujuan melindungi industri dalam negeri, akan tetapi terdapat Ã¬ndustri yang menginginkan produk tinplate tidak dikenakan anti-dumping karena produksi dalam negeri belum mencukupi. Penelitian ini menguji penerapan bea masuk anti-dumping terhadap produk tinplate dari China, Taiwan dan Korea selama tahun 2014 s.d. 2018, dengan tujuan mengetahui apakah ada perbedaan nilai importasi sebelum dan selama dikenakan bea masuk anti-dumping. Menggunakan data sekunder yang bersumber dari UNComtrade. Sampel dipilih negara yang secara kontinyu mengirim produk tinplate ke Indonesia sejak 2010 s.d. 2018, yaitu China, Taiwan, Korea, Jepang, Jerman, India dan Malaysia. Menggunakan Mean Equality Test, diketahui terdapat perbedaan nilai importasi sebelum dengan selama dikenakan bea masuk anti-dumping. Hasil penelitian menunjukkan bahwa nilai-P (p-value) adalah 0,0114 lebih kecil dari alpha (Î±=0,05), sehingga disimpulkan terdapat perbedaan pada nilai importasi produk tinplate sebelum dengan selama dikenakan bea masuk anti-dumping. Hasil analisis deskriptif menggambarkan importasi dari China dan Taiwan cenderung menurun sedangkan importasi dari Korea cenderung naik walaupun dikenakan bea masuk anti-dumping karena mampu bersaing dengan menggunakan tarif preferensi berdasarkan skema perdagangan bebas.Kata Kunci: Anti-dumping, Bea Masuk, tinplate